Dual-Objective Control of Maximum and Residual Drift Ratios of Super-Tall Buildings Based on Self-Centering Energy Dissipation Outriggers - Xie, Linlin; An, Nan; Wang, Xinyu; Liu, Qianmin; Yang, Cantian (Frontiers in Materials, 2022)
It is critical to ensure the seismic resilience of super-tall buildings using high performance materials. The seismic resilience of these buildings can be enhanced by simultaneously controlling the maximum and residual inter-story drift ratios. To realize such dual-objective control, a prevailing trend is to adopt self-centering energy dissipation outriggers. In this study, taking a real engineering practice as the prototype building, super-tall building study cases with energy dissipation outriggers and with self-centering energy dissipation outriggers are designed. Based on nonlinear time-history analysis, the seismic performances of these study cases are evaluated and compared with emphasis on the maximum and residual inter-story drift ratios. The dual-objective control effect of self-centering energy dissipation outriggers and energy dissipation outriggers are analyzed and compared. The results indicate that self-centering energy dissipation outriggers are more effective than energy dissipation outriggers for achieving the dual-objective control of the maximum and residual drift ratios of super-tall buildings.